Mechanical properties of tunneling nanotube and its mechanical stability in human embryonic kidney cells - Li, Aoqi; Han, Xiaoning; Deng, Linhong; Wang, Xiang (Frontiers in Cell and Developmental Biology, 2022)
Tunneling nanotubes (TNTs) are thin membrane tubular structures that interconnect physically separated cells. Growing evidence indicates that TNTs play unique roles in various diseases by facilitating intercellular transfer of signaling and organelles, suggesting TNTs as a potential target for disease treatment. The efficiency of TNT-dependent communication is largely determined by the number of TNTs between cells. Though TNTs are physically fragile structures, the mechanical properties of TNTs and the determinants of their mechanical stability are still unclear. Here, using atomic force microscope (AFM) and microfluidic techniques, we investigated the mechanical behavior and abundance of TNTs in human embryonic kidney (HEK293) cells upon the application of forces. AFM measurements demonstrate that TNTs are elastic structures with an apparent spring constant of 79.1±16.2 pN/µm. The stiffness and membrane tension of TNTs increase by length. TNTs that elongate slower than 0.5 µm/min display higher mechanical stability, due to the growth rate of F-actin inside TNTs being limited at 0.26 µm/min. Importantly, by disturbing the cytoskeleton, membrane, or adhesion proteins of TNTs, we found that F-actin and cadherin connection dominantly determines the tensile strength and flexural strength of TNTs respectively. It may provide new clues for screening TNT-interfering drugs that alter the stability of TNTs.